Samuel Beckett and the primacy of love - Keller, John (Manchester University Press, 2002)
This study is about the central place of the emotional world in Beckett's writing. Stating that Beckett is 'primarily about love', Dr. Keller makes a radical re-assessment of his influence and immense popularity. The book examines numerous Beckettian texts, arguing that they embody a struggle to remain in contact with a primal sense of internal goodness, one founded on early experience with the mother. Writing itself becomes an internal dialogue, in which the reader is engaged, between a 'narrative-self' and a mother. Keller suggests that this is Beckett's greatest accomplishment as an artist: to document a universal struggle that allows for the birth of the mind, and to connect this struggle to the origin, and possibility of the creative act. This study integrates highly readable discussions of psychoanalytic theory, as well as clinical examples. It will be of value to scholars and readers of Beckett, and anyone interested in his place in literature and culture.